The family-specific α4-helix of the kinesin-13, MCAK, is critical to microtubule end recognition - Patel, Jennifer T.; Belsham, Hannah R.; Rathbone, Alexandra J.; Wickstead, Bill; Gell, Christopher; Friel, Claire T. (Royal Society Publishing, 2016)
Kinesins that influence the dynamics of microtubule growth and shrinkage require the ability to distinguish between the microtubule end and the microtubule lattice. The microtubule depolymerizing kinesin MCAK has been shown to specifically recognize the microtubule end. This ability is key to the action of MCAK in regulating microtubule dynamics. We show that the a4-helix of the motor domain is crucial to microtubule end recognition. Mutation of the residues K524, E525 and R528, which are located in the C-terminal half of the a4-helix, specifically disrupts the ability of MCAK to recognize the microtubule end. Mutation of these residues, which are conserved in the kinesin-13 family and discriminate members of this family from translocating kinesins, impairs the ability of MCAK to discriminate between the microtubule lattice and the microtubule end.